Pickles and ice cream! Food cravings in pregnancy: hypotheses, preliminary evidence, and directions for future research - Orloff, Natalia C.; Hormes, Julia M. (Frontiers in Psychology, 2014)
Women in the United States experience an increase in food cravings at two specific times during their life, 1) perimenstrually and 2) prenatally. The prevalence of excess gestational weight gain (GWG) is a growing concern due to its association with adverse health outcomes in both mothers and children. To the extent that prenatal food cravings may be a determinant of energy intake in pregnancy, a better understanding of craving etiology could be crucial in addressing the issue of excessive GWG. This paper reviews the available literature to corroborate and/or dispute some of the most commonly accepted hypotheses regarding the causes of food cravings during pregnancy, including a role of 1) hormonal changes, 2) nutritional deficits, 3) pharmacologically active ingredients in the desired foods, and 4) cultural and psychosocial factors. An existing model of perimenstrual chocolate craving etiology serves to structure the discussion of these hypotheses. The main hypotheses discussed receive little support, with the notable exception of a postulated role of cultural and psychosocial factors. The presence of cravings during pregnancy is a common phenomenon across different cultures, but the types of foods desired and the adverse impact of cravings on health may be culture-specific. Various psychosocial factors appear to correlate with excess GWG, including the presence of restrained eating. Findings strongly suggest that more research be conducted in this area. We propose that future investigations fall into one of the four following categories: 1) validation of food craving and eating-related measures specifically in pregnant populations, 2) use of ecological momentary assessment to obtain real time data on cravings during pregnancy, 3) implementation of longitudinal studies to address causality between eating disorder symptoms, food cravings, and gestational weight gain, and 4) development of interventions to ensure proper prenatal nutrition and prevent excess GWG.